Association between Sleep Disturbances and Emotional/Behavioral Problems in Chinese and Japanese Preschoolers. Issue 3 (3rd May 2020) - Wang, Guanghai; Takahashi, Micho; Wu, Ran; Liu, Zhijun; Adachi, Masaki; Saito, Manabu; Nakamura, Kazuhiko; Jiang, Fan
ABSTRACT: Objectives : Sleep disturbances are often associated with emotional/behavioral problems in young children, but whether the association differs among Asian countries remains unknown. This study aimed to investigate the association between sleep disturbances and emotional/behavioral problems in Chinese and Japanese preschoolers and to explore potential differences. Methods : Participants were 1, 020 Chinese preschoolers from 10 cities and 438 Japanese preschoolers from 1 city aged 4 to 5 years. Parents filled out the Children's Sleep Habits Questionnaire (CSHQ) and the Strengths and Difficulties Questionnaire (SDQ). Results : Chinese children with sleep disturbances (defined as total CSHQ score >41) demonstrated more peer problems than children without, while there was no such difference in Japanese preschoolers. Domains of sleep disturbances associated with emotional/behavioral problems in Chinese children were sleep disordered breathing and daytime sleepiness, yet in Japanese children were sleep anxiety and night wakings. Children with a higher score of sleep anxiety showed more emotional problems in Japan, but fewer conduct problems in China. Conclusions : Sleep disturbances were associated with emotional/behavioral problems in preschoolers with differences between China and Japan, indicating subcultural differences in preschoolers' sleep within Asian countries. Abbreviations : CSHQ: Children's Sleep Habits Questionnaire; SDQ: Strengths and Difficulties Questionnaire; ANCOVA: analysis of covariance; SD: standard deviation; CI: confidence interval.